Characterization of retinal microvasculature and structure in atrial fibrillation - Liu, Junfeng; Tao, Wendan; Li, Dayan; Kwapong, William Robert; Cao, Le; Zhang, Xiaoling; Ye, Chen; Chen, Shi; Liu, Ming (Frontiers in Cardiovascular Medicine, 2023)
Background and objective: Very little is known about the retinal microvasculature changes in patients with atrial fibrillation (AF). Our study aimed to characterize the microvasculature and structure of the retina in AF patients and explore their differences in different subtypes. Methods: This cross-sectional study was conducted at the department of neurology and cardiology in West China hospital, Chengdu, China. Individuals aged 40 years or older with a diagnosis of AF were eligible for inclusion. Control individuals were aged 40 years or older and without a history of AF, ocular abnormalities/disease, or any significant systemic illness. The retinal vascular and structural parameters were assessed using swept-source optical coherence tomography (SS-OCT)/SS-OCT angiography (SS-OCTA). Meanwhile, echocardiographic data of left atrium (LA) diameter was collected. Results: A total of 125 participants (71 men [56.8%]; mean [SD] age, 61.98 [8.73]) with AF and 111 control participants (53 men [47.7%]; mean [SD] age, 62.31 [6.47]) were analyzed. In our AF cohort, there were 71 paroxysmal AF and 54 sustained AF patients. Decreased retinal microvascular perfusion (β coefficient = -0.08; 95% CI, -0.14 to -0.03) and densities (β coefficient = -1.86; 95% CI, -3.11 to -0.60) in superficial vascular plexus (SVC) was found in eyes of participants with AF. In regard to retinal structures, thinner ganglion cell-inner plexiform layer (GCIPL; β coefficient = -2.34; 95% CI, −4.32 to -0.36) and retinal nerve fiber layer (RNFL) thicknesses (β coefficient = -0.63; 95% CI, −2.09 to -0.18) were observed in the eyes of participants with AF. The retinal parameters did not differ significantly between paroxysmal and sustained AF (all P>0.05). However, significant interactions were observed between LA diameter and AF subtypes with the perfusion and densities in SVC(P<0.05). Conclusions: We found that individuals with AF had decreased retinal vascular densities and perfusion in SVC, as well as thinner GCIPL and RNFL thickness compared with controls. The differences of the retinal microvasculature in SVC between paroxysmal and sustained AF depending on LA diameter. Further studies are of interest to investigate the natural history of retinal microvascular and structural changes in individuals across the clinical process of AF and AF subtypes.